A Trojan Horse in the Citadel of Stories? - Hartley, John (Cultural Science, 2013)
Digital storytelling is an international movement for self-representation and advocacy, especially in educational, arts, and therapeutic communities. It has begun to attract a significant body of scholarship including publications and conferences. Australia has been an important player in all of these developments. In this presentation I explore some of the issues that have emerged for activists and scholars, including the problem of how to ‘scale up’ from self-expression to communication (i.e. self-marketing), and the question of the role that stories play in constituting ‘we’-communities (or ‘demes’). The paper pursues the relationship between storytelling and political narrative over the extreme long term (longue durée), using well known and lesser-known connections between Australia and Turkey to tell the tale. It considers how digital self-representation intersects with that political process, and what activists need to know in order to intervene more effectively. The paper is in five parts: (1) Gevinson; (2) Gallipoli; (3) Granddad; (4) Göbekli Tepe; (5) Gotcha? It seeks to place digital storytelling within a larger framework that links storytelling with the evolution of the polity. The analysis ultimately points to a looming problem for the digital storytelling movement – and possibly for human socio-cultural evolution too. In the crisis of ‘we’ communities that arises with the possibility of a globally networked polity, we need new guides to storytelling action, not the old (Trojan) warhorses of mainstream media. Events such as the centenary of World War I present unexpected opportunities for this kind of exploration.